Optimization of catalyst preparation conditions for hydrogen generation in the presence of Co-B using taguchi method - Sagir, Kadir; Elcicek, Huseyin; Ozdemir, Oguz Kaan (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Efficient hydrogen generation is a significant prerequisite of future hydrogen economy. Therefore, the development of efficient non-noble metal catalysts for hydrolysis reaction of sodium borohydride (NaBH4) under mild conditions has received extensive interest. Since the transition metal boride based materials are inexpensive and easy to prepare, it is feasible to use these catalysts in the construction of practical hydrogen generators. In this work, temperature, pH, reducing agent concentration, and reduction rate were selected as independent process parameters and their effects on dependent parameter, such as hydrogen generation rate, were investigated using response surface methodology (RSM). According to the obtained results of the RSM prediction, maximum hydrogen generation rate (53.69 L. min(-1)g(cat)(-1)) was obtained at temperature of 281.18 K, pH of 5.97, reducing agent concentration of 31.47 NaBH4/water and reduction rate of 7.16 ml min(-1). Consequently, after validation studies it was observed that the RSM together with Taguchi methods are efficient experimental designs for parameter optimization. (C) 2020 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Cobalt catalysts; Hydrogen production; Response surface methodology; Taguchi method; MACHINING PARAMETERS; FUEL; DESIGN; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels